132 Effects of Valbenazine on Depression and Suicidality in Adults With Tardive Dyskinesia: Pooled Results of 3 Double-Blind, Placebo-Controlled Trials. (15th June 2018) - Remington, Gary; Thai-Cuarto, Dao; Burke, Joshua; Siegert, Scott; Liang, Grace S.
Abstract: Study Objectives: Valbenazine (INGREZZA; VBZ) is a novel and highly selective vesicular monoamine transporter 2 (VMAT2) inhibitor that is approved for the treatment of tardive dyskinesia (TD) in adults. The randomized, double-blind, placebo (PBO)-controlled trials of VBZ evaluated the treatment of TD in patients with a primary psychiatric diagnosis (schizophrenia/schizoaffective disorder or mood disorder) while on concomitant psychiatric medications to manage these disorders. Since treatment-emergent depression and suicidal ideation/behavior are important clinical concerns in psychiatric patient populations, data from these trials were analyzed to assess the effectsof once-daily VBZ on depression and suicidality. Methods: Data were pooled from three 6-week trials: KINECT (NCT01688037), KINECT 2 (NCT01733121), KINECT 3 (NCT02274558). Outcome data were analyzed in the safety population by pooled VBZ doses (40 mg, 80 mg) and PBO. Outcomes of interest included: treatment-emergent adverse events (TEAEs) related to depression or suicidality; mean score change from baseline to Week 6 in the Calgary Depression Scale for Schizophrenia (CDSS, for participants with schizophrenia/schizoaffective disorder) or the Montgomery-Åsberg Depression Rating Scale (MADRS, for participants with mood disorder); and, worsening from baseline in Columbia-Suicide Severity Rating Scale (C-SSRS) suicidal ideation scores. All outcomes were analyzed descriptively. Results: There were 400 total participants in the pooled safety population; 286 participants had schizophrenia/schizoaffective disorder (40 mg, n=82; 80 mg, n=70; PBO, n=134) and 114 had a mood disorder (40 mg, n=28; 80 mg, n=42; PBO, n=44). Over one-third of participants had a lifetime history of suicidal ideation or behavior (40 mg, 45%; 80 mg, 39%; PBO, 37%). Few participants had a depression- or suicide-related TEAE, with no apparent differences between VBZ and PBO: suicidal ideation (40 mg, 3.6%; 80 mg, 0.9%; PBO, 2.2%); depression (40 mg, 0%; 80 mg, 1.8%; PBO, 1.1%); depressive symptom (40 mg, 0.9%; 80 mg, 0%; PBO, 0.6%); suicide attempt (40 mg, 0%; 80 mg, 0.9%; PBO, 0%). Mean changes from baseline to Week 6 in depression scale scores were generally small and similar across treatment groups: CDSS total score (40 mg, -0.5; 80 mg, -0.6; PBO, -0.3); MADRS total score (40 mg, -0.2; 80 mg, -1.7; PBO, 0.6). Few participants had a shift from no suicidal ideation at baseline (C-SSRS score=0) to any suicidal ideation during treatment (C-SSRS score=1-5): 40 mg, 3.9% (4/103); 80 mg, 0.9% (1/111); PBO, 2.9% (5/174). Conclusion: Data from 3 double-blind, placebo-controlled trials indicate that once-daily VBZ treatment was not associated with a worsening in depression-related symptoms or an increased risk of suicidal ideation or behavior. Funding Acknowledgements: This study was funded by Neurocrine Biosciences, Inc.